Agricultural Biotechnology: Potential, Constraints, and Policy Environment - Rosegrant, Mark W.; Spielman, David J.; Falck-Zepeda, Jose (2023)
Rosegrant, Mark; Spielman, David; and Falck-Zepeda, Jose. 2023. Agricultural Biotechnology: Potential, Constraints, and Policy Environment. PowerPoint presentation given to students of AG 4390/AG 5371: Global Agriculture Leadership Academy. Department of Agriculture, Texas State University, San Marcos, Texas, March 30, 2023.